Development of biosurfactant-based graphene quantum dot conjugate as a novel and fluorescent theranostic tool for cancer - Bansal S (Dove Medical Press, 2019)
Smriti Bansal,1 Joga Singh,2 Uma Kumari,3 Indu Pal Kaur,2 Ravi Pratap Barnwal,4 Ravinder Kumar,3 Suman Singh,5 Gurpal Singh,2 Mary Chatterjee1 1Biotechnology Engineering, University Institute of Engineering & Technology, Panjab University, Chandigarh, India; 2Department of Pharmaceutical Sciences, University Institute of Pharmaceutical Sciences, Panjab University, Chandigarh, India; 3Department of Zoology, Panjab University, Chandigarh, India; 4Department of Biophysics, Panjab University, Chandigarh, India; 5Department of Agronomics, Central Scientific Instruments Organisation, Chandigarh, India Background: Biosurfactants are amphipathic molecules of microbial origin that reduce surface and interfacial tension at gas–liquid–solid interfaces. Earlier, the biosurfactant was isolated and characterized in our laboratory from Candida parapsilosis. The property of the biosurfactant is further explored in this study by using quantum dots (QDs) as nanocarrier.Materials and methods: Graphene quantum dots (GQDs) were synthesized by bottom-up approach through pyrolysis of citric acid. GQDs were conjugated with both biosurfactant and folic acid (FA) using carbodiimide chemistry. The prepared GQD bioconjugate was studied for diagnostic and therapeutic effects against cancer cells.Results and discussion: Photoluminescence quantum yield (QY) of plain GQDs was measured as 12.8%. QY for biosurfactant conjugated GQDs and FA-biosurfactant conjugated GQDs was measured as 10.4% and 9.02%, respectively, and it was sufficient for targeting cancer cells. MTT assay showed that more than 90% of cells remained viable at concentration of 1 mg/mL, hence GQDs seemed to be non-toxic to cells. Biosurfactant conjugated GQDs caused 50% reduction in cellular viability within 24 hours. FA conjugation further increased the specificity of bioconjugated GQDs toward tumor cells, which is clearly evident from the drug internalization studies using confocal laser scanning microscopy. A higher amount of drug uptake was observed when bioconjugated GQDs were decorated with FA.Conclusion: The ability of GQD bioconjugate could be used as a theranostic tool for cancer. It is foreseen that in near future cancer can be detected and/or treated at an early stage by utilizing biosurfactant conjugated GQDs. Therefore, the proposed study would provide a stepping stone to improve the life of cancer patients. Keywords: bioconjugation, nanomedicine, nanocarrier, cancer therapy, folic acid receptor, graphene quantum dots